The Influence Of Brand Love On Brand Loyalty Through Self Esteem And Susceptibility To Normative Influence As Moderation Variables To Consumers Iphone Product Users In Padang City - Ario Rezki Wibowo; Yasri Yasri (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2023)
This study aims to analyze and prove the effect of brand love on brand loyalty through self-esteem and susceptibility to normative influence as moderating variables. This research was conducted on consumers who used iPhone products at least twice. The data used in this study is primary data obtained by distributing questionnaires to consumers who use iPhones in the city of Padang. The data analysis technique used in this study is the Structural Equation Model (SEM). Data processing is done with Partial Least Square (PLS). Based on the results of testing the hypothesis that has been done, it was found that brand love has a positive effect on brand loyalty. In addition, self-esteem and susceptibility to normative influence also affect consumer brand loyalty to iPhone products in Padang City. The results of the indirect influence test show that self-esteem and susceptibility normative influence are able to mediate the relationship between brand love and consumer brand loyalty in using iPhone products in Padang City.